Development of Inquiry-Based Student Worksheets on Ecosystem Materials for the High School Level - Waruwu, Dasari; Suzanti, Fitra; Mahadi, Imam (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to develop inquiry-based student worksheets to improve students’ critical thinking skills and learning motivation. This development research uses the ADDIE (analysis, design, development, implementation, and evaluations) method. The development of inquiry-based student worksheets is developed on ecosystem materials. The results of the development of inquiry-based Student Worksheets with validity tests obtained an average score of 3.58 with very valid categories, so they have excellent quality and are worthy of use. The results of the development of student worksheets and the teacher response practicality test obtained an average score of 92.83 in the very practical category. From the results of the practicality test obtained, inquiry-based Student Worksheets have very practical qualities. The results of the development of inquiry-based student worksheets have a significant influence on improving students’ critical thinking skills and learning motivation with a test significance value of t 0.000 <0.005. The results of the t-test on improving students' critical thinking skills showed a mean statistics percentage of 83.12 very critical categories. The results of the t-test on increasing student learning motivation showed a mean statistics percentage of 82.8 categories of highly motivated.